Magnetic, transport, and structural properties of SrRuO3 thin films - STAMENOV, PLAMEN; COEY, JOHN; RODE, KARSTEN (My University, 2014)
Thin films of the oxide ferromagnetic metal SrRuO3 (SRO) are studied, in view of their potential use within oxide-based spin electronic devices. Here, their epitaxial growth on Si-compatible SrTiO3 substrates is demonstrated by pulsed laser deposition. Detail on their initial, structural, magnetic, and magnetotransport characterisation is also provided. In particular, resistivity and Hall data are interpreted within a two/three carrier model, above T C. Below T C, some information about the anisotropy of the Fermi surface effective elipsoids (∼1:4) is recovered. The low-temperature saturation magnetisation approaches 1 μB/Ru, with an uniaxial anisotropy of above 0.6 MJm–3. Despite its low T C = 160 K, and in view of its relatively low carrier mobility, it is reasoned that SRO could be utilized as the electrode layer in low-temperature all-oxide-MTJ (Magnetic Tunnel Junction) demonstrators and as a seed layer for other ferromagnetic oxides, at and above room temperature.
PUBLISHED
Keywords: Thin films of the oxide ferromagnetic metal SrRuO3 (SRO); Thin films of the oxide ferromagnetic metal SrRuO3 (SRO)